2013
DOI: 10.1371/journal.pone.0075815
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 Expression Induces Myeloid Differentiation of Human Acute Leukemia Cells and Normal Hematopoietic Progenitors

Abstract: In acute myeloid leukemia (AML) and blast crisis (BC) chronic myeloid leukemia (CML) normal differentiation is impaired. Differentiation of immature stem/progenitor cells is critical for normal blood cell function. MicroRNAs (miRNAs or miRs) are small non-coding RNAs that interfere with gene expression by degrading messenger RNAs (mRNAs) or blocking protein translation. Aberrant miRNA expression is a feature of leukemia and miRNAs also play a significant role in normal hematopoiesis and differentiation. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 71 publications
5
39
0
Order By: Relevance
“…Notably, gene expression changes identified by RT-qPCR with KLF4 overexpression were similar to those we observed with miR-150 overexpression, in particular with regard to S100A8 and S100A9 (Fig. 2B) (22). KLF2 and KLF4 overexpression inhibited proliferation of THP-1 cells and induced expression of a known, and well-characterized, downstream target gene of KLF4, the cell cycle inhibitor CDKN1A, which in other work has been shown to limit cell proliferation and promote differentiation ( Fig.…”
Section: Klf4 Expression Is Decreased In Primary Patient Aml Casessupporting
confidence: 80%
See 3 more Smart Citations
“…Notably, gene expression changes identified by RT-qPCR with KLF4 overexpression were similar to those we observed with miR-150 overexpression, in particular with regard to S100A8 and S100A9 (Fig. 2B) (22). KLF2 and KLF4 overexpression inhibited proliferation of THP-1 cells and induced expression of a known, and well-characterized, downstream target gene of KLF4, the cell cycle inhibitor CDKN1A, which in other work has been shown to limit cell proliferation and promote differentiation ( Fig.…”
Section: Klf4 Expression Is Decreased In Primary Patient Aml Casessupporting
confidence: 80%
“…In AML primary patient samples and cell lines, we demonstrated that expression of miR-150 decreases cell proliferation and promotes myeloid differentiation (22). Our observations are supported by a study in which it was observed that miR-150 reexpression in an MLL-AF9 rearranged murine model of AML inhibited leukemia cell growth (23).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…In this context, Moles and coworkers [118] demonstrated that both miRNA-223 and miRNA-150 target STAT1 3′-UTR and reduce STAT1 expression, which in turn results in reduced expression of IFN-γ-regulated genes. The expression of miRNA-150 is upregulated in CD19 + B cells from chronic lymphocytic leukemia [119,120], while in chronic myeloid leukemia [121,122], ALL [123] and mantel cell carcinoma miRNA-150 is downregulated. Moreover, miRNA-150 is upregulated in adult T-cell leukemia/lymphoma cells.…”
Section: Control Of the Ifn-γ Pathway By Mirnasmentioning
confidence: 99%